Prejudice, friendship and the abuse of disabled people: an exploration into the concept of exploitative familiarity ('mate crime'). Issue 9 (20th October 2020) - Doherty, Gerard
Abstract: Exploitative familiarity ('mate crime') is a recently-identified phenomenon. Available evidence suggests that exploitative familiarity has a significant impact on the lives of some disabled people, not only in terms of the breadth of offences committed using this form of insidious exploitation but also because of the potential grave consequences. Often, isolated disabled people are victimised in their homes by locals who may use the effects of victims' impairments to manipulate and betray purported friendships. Exploitation can continue unchecked, particularly where there is lack of institutional involvement. Based on a case study of police records and drawing upon the fields of hate crime and disability studies, this article provides an explanation of how and why exploitative familiarity occurs. The evidence appears to suggest that oppression and stigmatisation of disabled people lead to relational disadvantages such as poverty and isolation. However, it is the 'individual vulnerability' of victims which directly influences targeting.